Calibrated Passive Microwave Daily EASE-Grid 2.0 Brightness Temperature ESDR (CETB) Algorithm Theoretical Basis Document, Version 1.0 ... - Brodzik, Mary J.; Long, David G. (Zenodo, 2018)
This technical document is the Algorithm Theoretical Basis Document for the NASA MEaSUREs Calibrated Passive Microwave Daily EASE-Grid 2.0 Brightness Temperature (CETB) Earth Science Data Record (ESDR) Version 1.0. The document describes the theory of several image reconstruction methods that were implemented, investigated and compared to produce the CETB ESDR, an enhanced-resolution, gridded passive microwave data set derived from a suite of satellite-borne sensors operating from 1978 to present. Two potential input swath data sets are compared. Complete Version 1 processing was performed on Colorado State University (CSU) Fundamental Climate Data Records (FCDRs). Version 1 data are managed and distributed at the NASA National Snow and Ice Data Center (NSIDC) Distributed Active Archive Center (DAAC). This ATBD contains the primary material that the NSIDC DAAC has used to compile the data user guide. ...